Analisis Faktor Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Netha Damayantie; Rusmimpong Rusmimpong; Mashudi Mashudi; Ririndia Ditiaharman (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the quality of life factors of chronic kidney failure patients undergoing hemodialysis. The research method used is analytic observational using a cross-sectional design. The results showed that the dominant quality of life in the medium category was 41 respondents (53.9%). The quality of life variable is related to knowledge (p-value = 0.002), family support (p-value = 0.001), motivation (p-value = 0.005), and BMI (p-value = 0.001). In conclusion, the quality of life of chronic kidney failure patients undergoing hemodialysis at Raden Mattaher Hospital Jambi is related to knowledge, family support, motivation, and Body Mass Index (BMI). Keywords: Kidney Failure, Hemodialysis, Quality of Life